Слушайте революцию !: стихи поэтов народов СССР / [сост. Ю. Н. Спасская, худ. Шагеев Э.] - Спасская Ю. Н. (Дет. лит., 1987)
Экземпляры: (20170517) / Инвентарный номер: 20050 / Цена: 2.50 / Авт.знак: С49 / ББК: 84(2Рос)